Chronic Diarrhea and Weight Loss in Kidney Transplant Recipients: Role of Norovirus - Abhishek Kadam; Sishir Gang; Abhijit Konnur; Umapati Hegde; Hardik Patel; Sachchida Nand Pandey (Indian Journal of Transplantation)
Background: Chronic and persistent diarrhea is a frequent problem in kidney transplant recipients. It is associated with weight loss, graft dysfunction and death. Norovirus has emerged as an important cause of chronic diarrhea in immunocompromised patients. We conducted this prospective study to determine the role of norovirus in kidney transplant recipients presenting with chronic and persistent diarrhea. Materials and Methods: Kidney transplant recipients presenting with chronic and persistent diarrhea between November 2019 and December 2020 were included in this study. Thorough clinical and laboratory evaluation was undertaken, including stool reverse transcription polymerase chain reaction (RTPCR) for norovirus. Patients were followed for 12 months. Results: Thirty-nine kidney transplant recipients presented with chronic and persistent diarrhea during the 12-month recruitment period. Twenty-nine patients had norovirus by RTPCR in their stools. The median duration of presentation post-kidney transplant was 63 months. The median duration of symptoms before inclusion in the study was 60 days. All patients had significant weight loss at presentation and 48% had acute graft dysfunction. Treatment approaches included reduction or withdrawal of antiproliferative medication. At 12 months of follow-up, 20 (69%) patients had improvement in diarrhea, weight gain was seen in 48% of patients and 31% of patients had a worsening renal function. There was persistent norovirus shedding in 9 of the 11 patients evaluated at 12 months. Conclusion: Norovirus is a common cause of chronic diarrhea in kidney transplant recipients. Diarrhea and weight loss associated with it improve with reduction in immunosuppression, but a significant number of patients have chronic graft dysfunction. In kidney transplant recipients presenting with chronic diarrhea and weight loss, we must investigate for norovirus infection. Early reduction of immunosuppression will ameliorate its impact on graft dysfunction and weight loss.